Law and the Chinese in Southeast Asia - Hooker, M. B. (Book collections on Project MUSE., 2002)
This collection of essays focuses on law and the diaspora Chinese. They show us a variety of answers to such questions as: what are the laws of China outside China; what are the laws of the Chinese in Southeast Asia; what were/are the laws for the Chinese in Southeast Asia; and is there a "Confucian Chinese"? The answers in some cases are reasonably certain but in others they are tentative and debatable. The legal material raises these issues in a way which is fundamental to diaspora studies ...